Structural Invariance of Learning Strategies – a Longitudinal Study - Mujagić, Amela (Array, 2010)
The paper presents a part of validation procedures pertaining to an adapted Croatian version of LIST – an instrument designed for the assessment of learning strategies (Wild and Schiefle, 1994). So far conducted evaluation procedures of this version (Sorić & Palekčić, 2002), showed similar (but not identical) factor structures compared to those found in the original questionnaire. Further-more, LIST proved to be useful in the assessment of general learning strategies, like the assessment of strategies employed while studying various course materials, and/or of specific strategies used over the time. The question of measurement invariance becomes critical when trying to test any prediction based on the learning approach conceptualization behind the scale construction. Following theoretical assumptions on contextual specificity of the learning process, this study tried to assess the amounts of variance in learning strategies due to stable individual differences and/or situational factors. Data on cognitive learning strategies used while preparing for a written exam were collected by LIST administered on 155 second year university students on two occasions, with a 7 weeks time lag. Internal consistency and reliability analyses of the instrument were performed within the context of classical test theory and the latent state-trait theory (Steyer et al., 1992). Measurement invariance of the scale as a function of time point was tested via longitudinal confirmatory factor procedures.